Pengaruh Pemberian Makanan Tambahan Biskuit pada Balita yang Berat Badan Kurang terhadap Peningkatan Berat Badan Balita di Puskesmas Rantau Selamat Aceh Timur Tahun 2024 - Dewi Intan Sari; Ester Simanullang (OBAT: Jurnal Riset Ilmu Farmasi dan Kesehatan, 2025)
Providing additional recovery food (PMT), especially for vulnerable groups, is one of the supplementation strategies in overcoming nutritional problems so that cases of malnutrition and malnutrition can be prevented. The aim of this research is to determine the effect of giving supplementary feeding (PMT) biscuits to underweight toddlers on increasing the weight of toddlers at the Rantau Selamat Community Health Center, East Aceh in 2024. This quasi-experimental research uses a one group pre-post test design, namely the existing research design. pretest before being given treatment and posttest after being given treatment. The sample for this research was the entire research population, namely 61 people. Based on the results of this research, the weight status of respondents before the implementation of the PMT program at the Rantau Selamat Community Health Center was underweight for 10 toddlers. The results of the paired T-test statistical test in the second month, the change in toddler's weight before and after PMT-P was shown by the value p=0.000 (p<0.05), so it can be concluded statistically that there is an effect of giving additional food (PMT) on weight status in underweight toddlers (aged 6-33 months). Through this research, it is hoped that it can provide education and increase insight to parents of suffering toddlers to pay more attention to the food intake they consume every day. So that toddlers get adequate nutritional intake in an effort to improve the child's nutritional status.